2004
DOI: 10.1103/physreve.70.025201
|View full text |Cite
|
Sign up to set email alerts
|

Alternative pathways of dewetting for a thin liquid two-layer film

Abstract: We consider two stacked ultrathin layers of different liquids on a solid substrate. Using long-wave theory, we derive coupled evolution equations for the free liquid-liquid and liquid-gas interfaces. Depending on the long-range van der Waals forces and the ratio of the layer thicknesses, the system follows different pathways of dewetting. The instability may be driven by varicose or zigzag modes and leads to film rupture either at the liquid-gas interface or at the substrate. We predict that the faster layer d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
219
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(227 citation statements)
references
References 22 publications
7
219
1
Order By: Relevance
“…In addition, the uniform state admits both sinuous (zigzag) and varicose perturbation modes, where the perturbed interfaces are in phase or in antiphase respectively. Fully nonlinear simulations elucidated that the film ruptured distinctly in either the upper layer or the lower layer (Pototsky et al 2004) but also demonstrated the existence of periodic (non-uniform) solutions that coarsen in time (Pototsky et al 2005(Pototsky et al , 2006. Further analysis of this system also uncovered oscillatorydewetting behaviour in the presence of surfactants (Fisher & Golovin 2007), while a classification of the distinct rupture modes was made by Ward (2011).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, the uniform state admits both sinuous (zigzag) and varicose perturbation modes, where the perturbed interfaces are in phase or in antiphase respectively. Fully nonlinear simulations elucidated that the film ruptured distinctly in either the upper layer or the lower layer (Pototsky et al 2004) but also demonstrated the existence of periodic (non-uniform) solutions that coarsen in time (Pototsky et al 2005(Pototsky et al , 2006. Further analysis of this system also uncovered oscillatorydewetting behaviour in the presence of surfactants (Fisher & Golovin 2007), while a classification of the distinct rupture modes was made by Ward (2011).…”
Section: Introductionmentioning
confidence: 99%
“…4.6d ) and so there are two temporal branches for the growth rate, one or both of which can become unstable across the parameter space (similar to Pototsky et al 2004). We note that the discriminant of (4.6a) can be shown to be strictly non-negative and thus the growth rate is always real, precluding the existence of travelling wave solutions.…”
Section: Linear Stability Analysismentioning
confidence: 99%
See 3 more Smart Citations